MULTILEVEL HEDGING FOR MIDDLE-REGIONAL POWER: INDONESIA ASCENT TOWARD POWERHOOD THROUGH HEDGING - Kusumadewi, Hemalia; Wiswayana, Wishnu Mahendra (Indonesian Association for International Relations, 2024)
The aim of this research is to understand how a middle-regional power, such as Indonesia, uses hedging to serve its interests and to address the lack of literature on Indonesian power and hedging. This research applies the concepts of ‘multilevel hedging’ and ‘hedging behavior’, along with a literature review method, to comprehend Indonesia's status and its hedging strategy and motives. The findings of this research indicate that hedging is not only employed for insurance and risk mitigation, but also as a means to build power. It was observed that for Indonesia, hedging is a tool to both enhance and maintain power, aligning with one of the primary objectives of Indonesian foreign policy.